Interpretasi Dan Ekspresi Dwarapala dalam Penciptaan Seni Lukis - Ja’far, Wanda Masyita; Kondra, I Wayan; Tjokropramono, I Gede Yosef (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2023)
At first glance, in every building on the island of Bali, we will find two doorman statues, starting from the experience of seeing and observing - the doorman statue or the Dwarapala statue which if examined more deeply has high value and philosophy. Its very unique shape can inspire our imagination about current phenomena and the effect of modernity on the pattern of people's lives that affect the form and culture of our ancestors. that the meaning of the Dwarapala statue is something that needs to be raised so that it can become a lesson and reflection on oneself when entering a room or, especially a holy place. The benefits that are expected from this writing are that it can add to the public's insight about relics that are rich in philosophical meaning and can provide freedom of imagination in increasing creativity in the creation of painting.